THE RELATIONSHIP BETWEEN THE LEADERSHIP STYLE OF THE MADRASAH HEADMASTER WITH PROFESSIONAL COMPETENCE AND TEACHER PERFORMANCE IN MAN 1 BOGOR REGENCY - Inayah, Hoerunisa; Rabbanie, Muhammad Dahlan; Arif, Suyud (TARBAWY : Indonesian Journal of Islamic Education, 2020)
Abstract. This article analyzes the leadership style of the headmaster of madrasah and its relationship with professional competence and teacher performance in MAN 1 Bogor Regency. This research aims to find a positive relationship between the leadership style of the madrasah headmaster and professional competence; to know the positive relationship  between the leadership style of madrasah headmaster and teacher performance; and, to know the  positive relationship between the leadership style of the madrasah headmaster and professional competence and teacher performance in MAN 1 Bogor Regency. The approach in this research was non-experimental quantitative approach with a correlational method. Based on the results of this study, it can be concluded that there is a strong or high correlation between the leadership style of the madrasah headmaster and professional competence and teacher performance in MAN 1 Bogor Regency. Abstrak. Artikel ini menganalisis gaya kepemimpinan yang diterapkan oleh kepala madrasah serta hubungannya dengan kompetensi profesional dan kinerja guru di madrasah Aliyah Negeri 1 Kabupaten Bogor. Upaya Penelitian ini bertujuan untuk mengetahui adanya hubungan yang positif antara gaya kepemimpinan kepala madrasah dengan kompetensi profesional; mengetahui adanya hubungan yang positif antara gaya kepemimpinan kepala madrasah dengan kinerja guru; dan mengetahui adanya hubungan yang positif secara bersama-sama antara gaya kepemimpinan kepala madrasah dengan kompetensi profesional dan kinerja guru di madrasah Aliyah Negeri 1 Kabupaten Bogor. Pendekatan dalam penelitian ini adalah pendekatan kuantitatif non eksperimental dengan metode korelasional. Berdasarkan hasil penelitian ini dapat ditarik kesimpulan bahwa terdapat korelasi yang kuat atau tinggi, maka dari itu dapat disimpulkan terdapat  hubungan yang positif dan signifikan secara kuat atau tinggi  antara gaya kepemimpinan kepala madrasah dengan kompetensi profesional dan kinerja guru di MAN 1 Kabupaten Bogor.